Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

Les femmes salariées dans l'Église catholique francophone du Québec : une analyse du rôle de l'idéologie et de ses mécanismes dans le maintien des rapports de pouvoir - Bazinet, Colette (Université du Québec à Montréal, 1994)
Keywords: IREF; amériques; discipline; mémoires/thèses; québec; régions géographiques; sciences humaines; sociologie; thématiques; travail

Innovation technologique et pratiques domestiques : analyse d'une expérience domotique - Beillan, Véronique (Sociétés contemporaines, 1994)
À partir du suivi sociologique d'une expérience domotique portant sur quinze logements du secteur HLM, cette étude traite des conditions d'appropriation sociale d'une nouvelle technologie domestique. Après un exposé de la méthode de recueil des données, basée sur la réalisation de trois vagues ď entretiens - réparties sur trois ans - auprès des ménages du lotissement domotique, l'article présente les premiers résultats ainsi que les nouvelles pistes de recherche à approfondir lors de la troisième et dernière phase du suivi. L'analyse comparative des deux premières vagues d'entretiens a permis de noter la permanence des attentes et des attitudes des ménages à l'égard de la domotique mais aussi le caractère hétérogène et ambivalent de ces dernières. Des freins ď ordre socio-économique et socio-culturel à l'intégration sociale de la technique ont été identifiés. Ainsi, des liens se dessinent entre l'automatisation des tâches et certains éléments tels que le statut et l'identité de la femme, l'organisation et la hiérarchisation des activités domestiques, les pratiques de délégation et ď externalisation du travail domestique.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; care; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Nomadic subjects: Embodiment and sexual difference in contemporary feminist theory - Braidotti, Rosi (Columbia University Press, 1994)
Nomadic Subjects plaide pour un nouveau type de pensée philosophique, qui inclurait les idées du féminisme et abandonnerait le mode hégémonique qui est conventionnellement adopté dans la haute théorie. La prose personnelle, surprenante et vivante de Braidotti insiste sur une intégration du féminisme dans le discours dominant. Les essais explorent les problèmes qui sont au cœur des débats féministes actuels, y compris la relation de l'épistémologie occidentale à la «question de la femme», le féminisme et l'éthique biomédicale, le féminisme européen et la façon dont les féministes américaines pourraient se rapporter aux mouvements européens.
Keywords: LGBTQIA2+; cours; discipline; europe; fem1000; genre; har4600; identités LGBTQIA2+; philosophie politique; post-structuralisme; premier cycle; régions géographiques; sciences humaines; soc2014; thématiques; épistémologie

La mise en forme des pratiques domestiques dans le travail de conception d'appareils électroménagers - Chabaud-Rychter, Danielle (Sociétés contemporaines, 1994)
Ce texte a pour objet les relations que les concepteurs d'appareils électroménagers établissent avec les pratiques domestiques au cours de leur travail. Il traite de la mise en forme des pratiques culinaires des femmes opérée par l'innovateur pour leur transmutation en opérations mécaniques d'appareils de cuisine. Divers processus par lesquels l'expérience pratique domestique est traduite pour être rendue lisible et façonnable dans le monde industriel sont ainsi mis en évidence. Puis on tente de montrer comment les activités domestiques sont prises en compte et reconfigurées dans le travail que fait l'innovateur sur les propriétés et les dispositifs des appareils offerts à la perception, à la réflexion et à la manipulation au cours de l'usage.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; care; cours; discipline; europe; france; patriarcat; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Le pouvoir dans les groupes de femmes de la région de Québec - Couillard, Marie-Andrée (Recherches sociographiques, 1994)
Les idéaux féministes d'égalité formulés au cours des années 1970 et 1980 sont aujourd'hui confrontés à des discours divers qui pénètrent les groupes de femmes. D'une part, la vision des technocrates les incite à accepter des fonctions instrumentales en retour d'un financement considéré essentiel par plusieurs. La majorité des groupes en sont ainsi venus à offrir des services qui se situent dans le prolongement de ceux offerts par le réseau de la santé et des services sociaux. À travers ces ajustements, les groupes de femmes ne se définissent plus seulement comme des lieux de conscientisation et de résistance, mais bien comme des groupes communautaires travaillant, de concert avec d'autres groupes communautaires, à l'amélioration du bien-être collectif. Les discours savants portant sur le féminisme, sur les conditions de sa mise en oeuvre ou sur le rapport entre l'État et le communautaire rejoignent eux aussi les militantes et affectent de façons diverses le portrait qu'elles tracent de leurs pratiques. C'est cet ensemble complexe dans lequel des rapports de force se nouent quotidiennement que nous voulons décrire et analyser ici.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; discipline; groupes de femmes; histoire et politique; militance; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Ces femmes qui ont bâti Montréal : la petite et grande histoire des femmes qui ont marqué la vie de Montréal depuis 350 ans - Darsigny, Maryse; Descarries, Francine; Kurtzman, Lyne; Tardy, Évelyne (Les éditions du remue-ménage, 1994)
Plus de 350 chroniques et illustrations, couvrant l’histoire de Montréal depuis sa fondation, répertoriant des réalisations dans tous les secteurs d’activités, des synthèses et des repères chronologiques précieux sous la plume alerte de plus de 150 collaboratrices: journalistes, historiennes, militantes féministes, chercheures, étudiantes, écrivaines…
Keywords: SAC; amériques; discipline; histoire; histoire des femmes*; histoire et politique; montréal; politique; québec; régions géographiques; sciences humaines; thématiques

Interventions féministes : parcours et perspectives - De Koninck, Maria; Pâquet-Deehy, Ann; Dennie, Maureen; Savard, Sylvie; Turgeon, Joane (Nouvelles pratiques sociales, 1994)
L'article présente une synthèse des résultats de deux recherches réalisées en concertation et portant sur l'intervention féministe dans les domaines de la santé et des services sociaux au Québec. Recensions d'écrits complétées par une collecte de données auprès d'intervenantes oeuvrant sur le terrain, les recherches ont permis de constater que l'intervention féministe se répand et se diversifie. À partir de ce constat, les auteures proposent des réflexions et soulèvent des questions sur la pertinence, les possibilités et les mécanismes pouvant favoriser la recherche théorique sur la base des pratiques.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; cours; discipline; intervention sociale; périodes historiques; québec; régions géographiques; santé; santé des femmes*; sciences humaines; thématiques; travail social; trs3500

A History of Our Own - Eaklor, Vicki L. (The Lesbian Review of Books, 1994)
Lesbians played a role in all phases of Grove development, albeit that of a minority in number and, usually, in terms of power and recognition. Newton devotes two chapters (of eleven) exclusively to lesbians, and this seems adequately proportional to the lesbian presence in the decades she covers. Importantly, the differences for women between the two eras -- 1930s to 1960 and 1960 to 1980 -- appear to be determined by class and ethnicity rather than by gender. In the earlier period, says Newton, the gay "girls" or "ladies" (Grovers' terms) "were an elite, privileged group who faced relatively little cultural exclusion or discrimination from their male peers" (204); and, she reminds us, in both eras "whatever problems 'girls' had with 'boys,' physical safety was not one of them" (204). Although they never completely shared in the camp sensibility, and not at all in the public sex of the "Meat Rack," then, Grove lesbians were on an even footing (except in numbers) as long as they were white, Protestant, moneyed, artistic/theatrical, and devoted to the "fun" ethos of the settlement (indeed, "party" meant costumes and drinking, never politics). At the opposite end of New York State from Buffalo is Cherry Grove, a gay community as different from that treated in Boots of Leather as the geography symbolizes. As Esther Newton describes it in Cherry Grove, Fire Island, it could be a typical "all-American" postwar town -- dominated by the sensibilities of elite WASP males benefiting from the prosperity of the 1950s and 1960s, and hostile at times to those perceived as outsiders (by race, gender, ethnicity) or interlopers (day-trippers, pretentious Pines neighbors). The crucial exception, of course, is that the elitist WASP men (and some women) who built the town were gay. For these reasons, my reactions divided according to my dual identity. As a historian, I found this book superb in every way: it is an engaging narrative of six decades of the area's development textured with insightful commentary on the larger context of American life and questions regarding how and why Cherry Grove originated and endured. However, the lesbian reader in me, although agreeing that the presentation is wonderful (it is actually more fluid and readable than Boots of Leather), reacted to the sexism, racism, anti-Semitism, and classism that have characterized this community at various stages of its existence, and especially to the community's dismissal of women. As Newton herself summarizes in a passage concerning the "invasion" of the neighboring Pines community, "Whatever the Queen's function -- selling tickets to a play or blessing the bathers -- she also is the Grove, its key symbol and core representation" (269; italics in the original); and she adds in the accompanying endnote, "The normal processes of Grove action and narration tend to marginalize or even erase women" (345, n.7)
Keywords: discipline; histoire; histoire et politique; personnes lesbiennes; ressource en ligne; sciences humaines; sexualité; thématiques

Chloe plus Olivia: An anthology of lesbian literature from the seventeenth century to the present - Faderman, Lillian (Viking, 1994)
Dans Chloe Plus Olivia, Lillian Faderman ne cherche rien de moins à redéfinir radicalement quatre siècles de littérature lesbienne, répondant à un besoin longtemps négligé : une anthologie littéraire d'écrivains lesbiens des quatre derniers siècles, chaque pièce étant située dans un contexte historique et littéraire. Cet ouvrage de recherche historique propose une revue éclairante du concept changeant de « littérature lesbienne », suivi d'exemples de six genres différents : l'amitié romantique, l'inversion sexuelle, les lesbiennes exotiques et maléfiques, l'encodage lesbien, le féminisme lesbien et le féminisme post-lesbien. Faderman examine des œuvres aussi diverses que My Antonia de Willa Cather et Orlando de Virginia Woolf ; poésie de Gertrude Stein et Amy Lowell ; fiction de Carson McCullers, Helen Hull et Alice Walker. De plus, Chloe Plus Olivia contient des écrits d'hommes axés sur les relations entre femmes. Ces écrits sont inclus dans la première section du livre et ont été, à divers égards, importants pour le développement de la littérature lesbienne, puisque les hommes étaient beaucoup plus susceptibles que les femmes d'être publiés au cours des autres siècles. Il serait impossible d’identifier une seule « grande tradition » d’écriture lesbienne, car elle est en constante métamorphose, reflétant l’évolution des attitudes sociales et des voix des femmes. Chloe Plus Olivia , avec sa portée historique renforcée par la recherche personnelle de Faderman pour une définition de la littérature lesbienne, en fait le premier livre du genre ; il deviendra certainement le point de référence à partir duquel partiront toutes les études ultérieures sur la littérature lesbienne.
Keywords: arts; discipline; histoire; histoire et politique; littérature; outils; ouvrages de références; personnes lesbiennes; sciences humaines; thématiques; études littéraires

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

Volatile bodies: toward a corporeal feminism - Grosz, E. A. (Theories of representation and difference, 1994)
Volatile Bodies demonstrates that the sexually specific body is socially constructed: biology or nature is not opposed to or in conflict with culture. Human biology is inherently social and has no pure or natural "origin" outside of culture. Being the raw material of social and cultural organization, it is "incomplete" and thus subject to the endless rewriting and social inscription that constitute all sign systems. Examining the theories of Freud, Lacan, Merleau-Ponty, Foucault, Deleuze, Derrida, etc. on the subject of the body, Elizabeth Grosz concludes that the body they theorize is male. These thinkers are not providing an account of "human" corporeality but of male corporeality. Grosz then turns to corporeal experiences unique to women--menstruation, pregnancy, childbirth, lactation, menopause. Her examination of female experience lays the groundwork for developing theories of sexed corporeality rather than merely rectifying flawed models of male theorists.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; lit4700; premier cycle; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1994)
The Women's Arts Society of Montreal was founded in 1894 by Mary Martha Phillips and Mrs. James H. Peck (nee Mary Alice Skelton). The parent body of the Society (The Women's Art Association of Canada) was incorporated in Toronto in 1892. The goal of the Montreal Society was to integrate women into the art world at a time in history when women had few rights and were relegated to other roles. In 1907, the Montreal branch of the Women's Art Association of Canada broke away from the Toronto organization to form their own independent society. During and after the First World War, the Women's Arts Society of Montreal focussed on philanthropic efforts, assisting disabled and convalescing veterans and their families. After 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In the late 1990s the Society began to accept men as members.
Keywords: 1800-1899; 1900-1999; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montréal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

L'identité féminine : biologie ou conditionnement social? - Irigaray, Luce (Femmes : moitié de la terre, moitié du pouvoir, 1994)
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; europe; fem1000; france; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes

L'énigme de la femme : la femme dans les textes de Freud - Kofman, Sarah (Librairie générale française, 1994)
Freud devant l'énigme de la femme. Ombres et mystères. Questions et suggestions. A partir d'une minutieuse exploration de l'ensemble des textes freudiens, Sarah Kofman souligne les ambiguïtés du fondateur de la psychanalyse quand il aborde le problème de la féminité. Et notamment l'étrangeté de son attitude, faite d'atermoiements et de résistances, où l'embarras et l'inquiétude semblent finalement l'emporter sur l'esprit de rigueur dont il se réclamait. Au bout du compte, explique Sarah Kofman, les réponses données par Freud relèvent de la spéculation. Plus que des réponses, même, ce sont des solutions-écran qui servent de couverture à ce qui ne saurait être regardé en face : le sexe de la femme, de la mère. La fameuse envie du pénis, cette " idée fixe " de Freud, est l'une des pseudo-solutions, destinée à fixer la femme dans une position immuable, à maîtriser son caractère, son instabilité, sa mobilité qui la rendent inaccessible, effrayante, énigmatique : " criminelle " aux yeux des hommes. L'Enigme de la femme ou la psychanalyse revisitée.
Keywords: 1900-1999; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; patriarcat; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; systèmes d'oppressions

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis

Sexualité et séropositivité : représentations sociales de femmes séropositives au virus de l'immunodéficience humaine (VIH) - Mensah, Maria Nengeh (Université du Québec à Montréal, 1994)
Keywords: 1900-1999; 1990-1999; IREF; VIH; discipline; mémoires/thèses; périodes historiques; santé; sciences humaines; sexologie; sexualité; thématiques

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques